ADJECTIVE CLAUSES AND ADVERBIAL CLAUSES IN “THE SECRET GARDEN” BY FRANCES HODGSON BURNETT - Apen Sumardi; Mashadi Said (INFERENCE: Journal of English Language Teaching, 2020)
This research aims to analyze the adjective and adverbial clauses in “The Secret Garden” by Frances Hodgson Burnett. The method used in this research is a content analysis which is to describes the adjective clause and adverbial clause in the novel. Data are obtained, analyzed, and described based on the sentences in the novel. The relative pronoun's adjective shows the highest percentage of 130 or 86%, while relative adverbs show 22 or 14%. The adjective clause in relative pronouns shows the highest percentage caused by the complex sentences, mostly describing someone or things in most sentences in the novel. Meanwhile, adjective clause in time shows 154 or 63%, manner 46 or 19%, reason 35 or 14%, condition 6 or 2%, and concession 4 2%. Adverbial clause in time shows the highest percentage caused by most sentences tell about the time in almost every page.